The Black Situation: Notes on Black Critical Theory Now. (22nd February 2022) - Reed, Anthony
Abstract: This essay argues that what some critics have dubbed an ontological turn in Black critical theory—the tendency to theorize racial antagonisms in general and antiblackness in particular as a function of the "being" of the West—reflects a more general pessimism endemic to our historical moment. That pessimism has been catalyzed by the collapse of meaningful alternatives in the postcolonial, post-communist moment, which results in occluded or obscured pathways to collective striving and worldmaking. One important response to the ontological turn has seen critics turn to Black culture to highlight peculiar modes of subjectivity shaped, but not defined by, ongoing racial antagonism. As Black particularity in this account remains implicit or intuitive, insofar as Black particularity remains a given rather than theorized, this tendency proves to be the other's flipside rather than alternative. This essay concludes by proposing that rather than studying culture to understand Black life, one study Black life to understand cultural production. The titular "Black situation" is its term for historical materialist analysis attuned to the complex modalities through which racial antagonism appears in daily life as well as the compulsions that impede sovereign individual agency.